1996
DOI: 10.1111/j.1530-0277.1996.tb01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptors in the Frontal Cortex of Alcoholics

Abstract: This study tests the hypothesis that glutamate receptors are altered in the brains of alcoholics as a result of chronic alcohol neurotoxicity. Release of the neurotransmitter glutamate after seizures or brain ischemia may damage postsynaptic neurons by increasing calcium flux through N-methyl-D-aspartate (NMDA) receptor-gated ion channels. Alcohol has two opposite effects on glutamate receptor ion channel complexes, depending upon the duration of exposure. Acute exposure to alcohol inhibits ion flow through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 39 publications
(3 reference statements)
0
50
0
Order By: Relevance
“…According to earlier reports, it was observed in both in vivo and in vitro studies that chronic ethanol treatment leads to an increase in the density of NMDARs leading to facilitated receptor functions [62,64,88,89,90,147,215]. However, up-regulation of NMDAR expression has not been found in all studies after chronic ethanol exposition [55,186].…”
Section: Effect Of Long-term Ethanol Exposure On the Structure Of Nmdarsmentioning
confidence: 69%
“…According to earlier reports, it was observed in both in vivo and in vitro studies that chronic ethanol treatment leads to an increase in the density of NMDARs leading to facilitated receptor functions [62,64,88,89,90,147,215]. However, up-regulation of NMDAR expression has not been found in all studies after chronic ethanol exposition [55,186].…”
Section: Effect Of Long-term Ethanol Exposure On the Structure Of Nmdarsmentioning
confidence: 69%
“…Upregulation of NMDA receptors by chronic ethanol administration may contribute to the altered sensitivity to ketamine effects observed in patients in this study. However, preclinical (Kalluri et al, 1998) and clinical (Freund and Anderson, 1996) studies suggest that increased NMDA receptor binding attributable to chronic ethanol administration is time-limited. Thus, ethanol-related NMDA receptor upregulation may play a greater role in acute rather than protracted withdrawal.…”
Section: Commentarymentioning
confidence: 99%
“…Sustained or chronic administration of ethanol and other NMDA receptor antagonists increases the mRNA or protein levels of some NMDA receptor subunits and the density of ligand binding to NMDA receptors in rodents and in cell lines (Darstein et al, 2000;Follesa and Ticku, 1996a, b;Gulya et al, 1991;Hu et al, 1996;Hu and Ticku 1995;Kalluri et al, 1998;Snell et al, 1996Snell et al, , 1993Trevisan et al, 1994). In post-mortem studies, NMDA receptor upregulation is associated with human ethanol dependence (Freund and Anderson, 1996;Michaelis et al, 1993). Preclinical studies suggest that this NMDA receptor upregulation contributes to ethanol tolerance and the complications of ethanol withdrawal, including seizures and neurotoxicity (Crews et al, 1999;Hoffman et al, 1990;Thomas and Morrisett, 2000;.…”
Section: Introductionmentioning
confidence: 99%
“…The result of which is reduced sensitivity to ethanol that is believed to contribute to alcohol tolerance (Krystal et al, 2003c). This is evidenced by postmortem studies of people with alcohol dependence that found an increased binding capacity of NMDA receptors in cortical tissue (Freund and Anderson, 1996), suggesting that a greater amount of alcohol is required to elicit the same effect.…”
Section: Alcohol and Nmda Receptorsmentioning
confidence: 74%
“…Notably, the same study found no differences in binding capacity at AMPA and kainite receptors between groups, highlighting the specificity of these effects (Freund et al, 1996).…”
Section: Alcohol and Nmda Receptorsmentioning
confidence: 89%